Assessment of vice-chancellors’ role performance in management of students’ welfare services in universities of North-East Zone, Nigeria - Garba, S. Danmaitaba; Abdulhakeem, U. Sidi; Hamza , M. Abubakar (Kashere Journal of Education, 2023)
This study was designed to assess the Vice-Chancellors’ Role Performance in Management of Students’ Welfare Services in Universities in North-East Zone, Nigeria. The study was conducted with two objectives which were to assess: The Vice-Chancellor’s role performance in management of students’ hostel accommodation services, the Vice-Chancellors’ role performance in management of security services in Universities in North-East Zone, Nigeria. `A descriptive survey research design was employed for the study. The population of the study comprises of all the fifteen Universities in North-East Geopolitical Zone of Nigeria. A multistage sampling technique was used for the study. Firstly, a purposeful sampling technique was used in the selected 6 universities out of the fifteen university for the study, similarly, a total of 75 staff were selected purposively both students’ affairs division and management staff, in the same vein, a total of 300 students comprises of hostel representatives and class representatives were selected which give a total of 420 respondents respectively. A structured questionnaire titled: ‘Opinion of Staff and Students’ in Management of Hostel Accommodation and Security Services ‘Questionnaire’ (SSMHASSQ). Questionnaire was developed by the researcher and validated by three experts in the Department of Educational Foundations and Curriculum Ahmadu Bello University, Zaria. The reliability coefficient of the validated instrument used for data collection for the study was 0.76 through Cronbach Alpha statistics. Mean and standard deviation were the statistical instrument used for answering the reach questions; while Analysis of Variance (ANOVA) was used test the hypotheses at .05 level of significance. The findings of the study revealed that Vice-Chancellor ensured that students’ hostel accommodation had facilities such as toilets and toiletries, bed space, good light facilities, Solar power systems are installed in the hostel premises for security, security personnel were stationed in the strategic areas to protect students and staff from the current trend of kidnapping, theft in the universities in the North-East zone, Nigeria. It was therefore concluded that the Vice-Chancellor paid little attention to students ’ welfare services in universities in the Nort-East. Adequate hostel accommodation should be provided for the students in the universities in the North-east, more sanitary facilities should be provided to students’ hostel to improve their well-being; In terms of security issues, the Vice-Chancellors should ensure that the security unit is provided with security van well equipped with communication gadgets. Also, Vice-Chancellors should ensure that security personnel are trained to handle campus security threat in the universities in the North-East zone of Nigeria.